A review on cellular senescence and prospect of Senolytic drugs against chronic age-related diseases - Tasnim, Saida Masuma (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.